1995
DOI: 10.1177/107755879505200302
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Hysterectomy: Variation within and Across Hospitals

Abstract: This study investigates the factors associated with the probability of finding specific clinical indicators (benign or malignant tumor, cancer in situ, fibroid, abscess/empyema, or positive culture of salpinx, fallopian tube, fetus, or uterus) that validate necessity for hysterectomy. Data for the 4,660 cases in the study come from 42 Pennsylvania hospitals. The probability that validating indicators were present varied significantly at the hospital level but not at the level of individual surgeons within hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The con®rmation of the second prediction is especially critical: where doctors work in different hospitals with different (procedure-speci®c) lengths of stay, intradoctor variation can be observed, that is to say that doctors choose a length of stay in the direction of the standard of the hospital in which they are working at the time. Arndt, Bradbury, and Golec recently showed that surgeons within medical teams do not vary in their policy on when it is appropriate to perform a hysterectomy, but between teams in different hospitals they observed large variations (23).…”
Section: Orientation Towards Local Standardsmentioning
confidence: 99%
“…The con®rmation of the second prediction is especially critical: where doctors work in different hospitals with different (procedure-speci®c) lengths of stay, intradoctor variation can be observed, that is to say that doctors choose a length of stay in the direction of the standard of the hospital in which they are working at the time. Arndt, Bradbury, and Golec recently showed that surgeons within medical teams do not vary in their policy on when it is appropriate to perform a hysterectomy, but between teams in different hospitals they observed large variations (23).…”
Section: Orientation Towards Local Standardsmentioning
confidence: 99%
“…Hysterectomy has long been a poster child for unexplained area-based variation. For example, rates differ across regions, within states, and between medical facilities 615 . Of the small literature on area-level correlates of hysterectomy use in the US, a Los Angeles-based study found higher median family income and percent non-White residential population were positively associated with higher area-level hysterectomy rates 7 .…”
Section: Introductionmentioning
confidence: 99%
“…A study on variation in length of hospital stay showed that variation within a medical team is small, compared to variation between teams (Westert, 1992). Hence, similarities are patterned by hospitals (Arndt, Bradbury, & Golec, 1995;Westert, Nieboer, & Groenewegen, 1993).…”
Section: Introductionmentioning
confidence: 99%